The Association of Emotion Regulation Strategies with Psychological and Physical Health among Low-Income Families - Aisha Amin; Dr. Muhammad Anis ul Haque (Research Journal of Psychology, 2025)
Background: Due to poverty youths from poor families’ struggle mostly in matters, concerning emotional self-control and this will major in either way affect psychological or physical well-being. There is a need to have better ways to manage stress that well known to have severe impacts on the human being. However, relatively little known about how these strategies affect the wellbeing of disadvantaged adolescents particularly in terms of their mental and physical health. Aim: The study sought to examine the association of emotion regulation strategies with psychological and physical health among adolescents from low-income families. Method: In this cross-sectional descriptive design, 500 adolescents of low-income families were included. Self-reported questionnaires assessed emotion regulation strategies, psychological health and physical health indices. Cross-tabulations along with comparisons and regression tests performed to compare the relations between the variables. Results: Adaptive strategies was positively correlated with psychological health, with r = 0.25, p < 0.01) while poor physical health was significantly predicted by maladaptive strategies with β = -0.146, p = 0.001). Therefore, regression analyses showed that there was significant amount of variance in psychological and physical health indices that was explained by the ER strategies; F (4, 268) = 22.28, p < .001; η² = .258, p < .001. Conclusion: Consequently, the results support the need for developing and advocating for efficient regulation of emotion to improve psychological and physical well-being of students from low-income families. Such findings indicate that enhancing the mechanism in this category of people may help enhance their general quality of life.